Constructing pedagogy: The nexus between artistic practice, research and teaching - Bennett, Dawn; Blom, D. (ASME, 2011)
This paper draws on the results of research with artist academics – artists employed as academics within universities principally to teach artistic skills - over a period of almost four years. Through this research we have sought to understand the experience of working in academia within an artistic discipline, one of which has been music. Effective music education is shaped by a complex set of relationships, including those between the musician as educator, practitioner and researcher. Within the higher education environment, all three activities are increasingly required, and we argue that the link, or nexus, between practice, research and teaching cannot be denied. Specifically, we ask: How does the knowledge contained within the process and product of artistic practice construct and inform pedagogy within undergraduate and postgraduate university teaching programs? In responding to this question, the paper draws on a diverse literature including our own previous research.